Effect of Maternal Age on Androstenedione and Pregnenolone Levels and Relationship with Retrieved Oocytes in Iraqi Women - Rusul Hashem; Nabaa Al-Nawab; Hala Baher; Farah Thamer Samawi (Bogor Agricultural University, Indonesia, 2026)
Follicular fluid (FF) entails a substantial number of steroids produced by granulosa cells (GCs) and theca cells, which are essential for developing oocytes. Nevertheless, it remains unclear how endogenous steroids in the FF change with advancing maternal age, which can affect oocyte maturation, subsequent embryo growth, and pregnancy outcomes after in vitro fertilization (IVF). Therefore, the aims of the present study are: (1) to examine the impact of maternal age on steroid (androstenedione A and pregnenolone P) levels in FF. (2) to test their association with IVF outcomes over age. (3) to assess whether these steroids are capable of forecasting pregnancy after IVF treatment. Forty women aged 36 to 47 are classified as the older group, and forty women aged 25 to 35 are classified as the younger group. The FF samples were drawn when the oocytes were picked up and steroidized. Steroid (A and P) levels were quantified using a Fa/Fs sandwich enzyme-linked immunosorbent assay (ELISA). A significant decline in the two selected steroid levels was observed in FF from the older women compared with those from the younger women (P<0.05). Steroid levels were positively associated with retrieved oocytes over time (P<0.05). Still, they did not achieve statistical significance with cleaved embryos (P>0.05) and did not have a predictive effect on pregnancy. Older women may have declined steroids and perturbed granulosa/theca cells' steroidogenesis, which subsequently perturbs oocytes and ovarian function, proposing a pathophysiology for the reduction in female reproductive capacity.